Effector-Specific Characterization of Brain Dynamics in Manual vs. Oculomotor Go/NoGo Tasks - Simonet, Marie; Ruggeri, Paolo; Barral, Jérôme (Frontiers in Human Neuroscience, 2020)
Motor inhibitory control (IC), the ability to suppress unwanted actions, has been previously exposed to rely on domain-general IC processes that would be involved across a wide range of IC tasks. Nevertheless, the existence of effector-specific regions and activation pattern that would differentiate manual versus oculomotor response inhibition remains unknown. In this study, we investigated the brain dynamics supporting these two response effectors with the same IC task paradigm. We examined the behavioral performance and the electrophysiological activity in a group of healthy young people (n=25) with a Go/NoGo task using the index finger for the manual modality and the eyes for the oculomotor modality. By computing topographic analysis of variance, we found significant differences between topographies of scalp recorded potentials of the two response effectors between 250 and 325 ms post-Nogo stimulus onset. The sources estimations localized this effect within the left precuneus, a part of the superior parietal lobule, showing stronger activity in the oculomotor modality compared to the manual modality. Behaviorally, we found a significant positive correlation in the response time between the two modalities. Our collective results revealed that, while domain-general IC processes would be engaged across different response effectors in a same IC task, there exists effector-specific activation patterns. In this case, the stronger activation of the left precuneus likely accounts for the increased demand of visual attentional processes in the oculomotor Go/NoGo task.